Modeling toothpaste brand choice: an empirical comparison of artificial neural networks and multinomial probit model - Kaya, Tolga; Aktas, Emel; Topçu, Ilker; Ulengin, Burç (Atlantis Press: Part of Springer Nature, 2010)
The purpose of this study is to compare the performances of Artificial Neural Networks (ANN) and Multinomial Probit (MNP) approaches in modeling the choice decision within fast moving consumer goods sector. To do this, based on 2597 toothpaste purchases of a panel sample of 404 households, choice models are built and their performances are compared on the 861 purchases of a test sample of 135 households. Results show that ANN's predictions are better while MNP is useful in providing marketing insight.
Change of publisher from Taylor & Francis to Atlantis Press: Part of Springer Nature
Keywords: Brand choice modeling; artificial neural networks; multinomial probit; toothpaste; household panel